Using and Curating Archaeological Collections - Warner, Mark S.; Warner, Mark S.; Childs, S. Terry; Childs, S. Terry (Book collections on Project MUSE., 2019)
All archaeologists have responsibilities to support the collections they produce, yet budgeting for and managing collections over the length of a project and beyond is not part of most archaeologists' training. While this book highlights major challenges that archaeologists and curators face with regards to collections, it also stresses the values, uses, and benefits of collections. It also demonstrates the continued significance of archaeological collections to the profession, tribes, and the public and provides critical resources to aid archaeologists in carrying out their responsibilities. Many lament that the archaeological record is finite and disappearing. In this context, collections are even more important to preserve for future use, and this book will help all stakeholders do so. --